2023
DOI: 10.4274/jcrpe.galenos.2022.2022-4-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Thyroid Elastography in Healthy Children and Patients with Hashimoto’s Thyroiditis

Abstract: Objective: Hashimoto’s thyroiditis (HT) is the most common form of thyroiditis in childhood. In addition to thyroid ultrasonography, shear-wave elastography (SWE) can evaluate thyroid parenchyma tissue stiffness, and more detailed findings can be obtained with this method. We aimed to evaluate the relationship between SWE values and clinical, biochemical and hormonal parameters of patients with HT and in healthy individuals. Methods: We compared 46 newly diagnosed HT ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…In another study in which factors affecting thyroid elastography by comparing children with HT with healthy controls, a positive correlation has been found with age, BMI SDS, and TPOAb. 9 There are other studies in the literature regarding a positive correlation between SWE scores with age and TPOAb. 3 , 10 , 11 In our current study, we observed a positive correlation between thyroid autoantibodies, age or other parameters that increase with age (body weight, height, BMI, thyroid volume), BMI SDS, and SWE scores.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In another study in which factors affecting thyroid elastography by comparing children with HT with healthy controls, a positive correlation has been found with age, BMI SDS, and TPOAb. 9 There are other studies in the literature regarding a positive correlation between SWE scores with age and TPOAb. 3 , 10 , 11 In our current study, we observed a positive correlation between thyroid autoantibodies, age or other parameters that increase with age (body weight, height, BMI, thyroid volume), BMI SDS, and SWE scores.…”
Section: Discussionmentioning
confidence: 98%
“… 3 , 14 , 15 In 1 study, the factors affecting SWE scores in individuals with HT, in the control group, and in the whole group were evaluated separately. 9 Influencing factors were also examined by multivariate regression analysis, and it was observed that only age, BMI SDS, and anti-TPO had an effect on the thyroid elasticity score in the regression model. 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional thyroid parameters were also measured. Three studies found significantly higher thyroid volume in HT [ 15 - 17 ], two higher TSH levels [ 7 , 8 ], four higher anti-TPO levels [ 7 , 8 , 16 , 17 ], and three anti-TG levels [ 7 , 16 , 17 ]. Additional study characteristics are detailed in Table 1 .…”
Section: Reviewmentioning
confidence: 99%
“…Hashimoto’s thyroiditis (HT) is one of the most prevalent autoimmune diseases, with the highest incidence rate among autoimmune thyroid disorders. 1 Studies have revealed the annually increasing incidence of HT. In China, the prevalence of HT ranges from 0.2% to 1.3%.…”
Section: Introductionmentioning
confidence: 99%